The effect of rock composition on cyanobacterial weathering of crystalline basalt and rhyolite - Olsson-Francis, K.; Simpson, A.; Wolff-Boenisch, Domenik; Cockell, C. (2012)
The weathering of volcanic rocks contributes significantly to the global silicate weathering budget, effecting carbon dioxide drawdown and long-term climate control. The rate of chemical weathering is influenced by the composition of the rock. Rock-dwelling micro-organisms are known to play a role in changing the rate of weathering reactions; however, the influence of rock composition on bio-weathering is unknown. Cyanobacteria are known to be a ubiquitous surface taxon in volcanic rocks. In this study, we used a selection of fast and slow growing cyanobacterial species to compare microbial-mediated weathering of bulk crystalline rocks of basaltic and rhyolitic composition, under batch conditions. Cyanobacterial growth caused an increase in the pH of the medium and an acceleration of rock dissolution compared to the abiotic controls. For example, Anabaena cylindrica increased the linear release rate (R i l) of Ca, Mg, Si and K from the basalt by more than fivefold (5.21-12.48) and increased the pH of the medium by 1.9 units. Although A. cylindrica enhanced rhyolite weathering, the increase in R i l was less than threefold (2.04-2.97) and the pH increase was only 0.83 units. The R i l values obtained with A. cylindrica were at least ninefold greater with the basalt than the rhyolite, whereas in the abiotic controls, the difference was less than fivefold. Factors accounting for the slower rate of rhyolite weathering and lower biomass achieved are likely to include the higher content of quartz, which has a low rate of weathering and lower concentrations of bio-essential elements, such as, Ca, Fe and Mg, which are known to be important in controlling cyanobacterial growth. We show that at conditions where weathering is favoured, biota can enhance the difference between low and high Si-rock weathering. Our data show that cyanobacteria can play a significant role in enhancing rock weathering and likely have done since they evolved on the early Earth. © 2012 Blackwell Publishing Ltd.